Influence of ethnicity on cultural use of pangolins in Ghana and its implications on their conservation - Boakye, Maxwell Kwame (Ethnobiology and Conservation, 2018)
Ethnicity has been documented to have an influence on the selection of medicinal resources and food. Pangolins are scaly mammals widely used for traditional medicine and consumed as bushmeat among local communities across Africa, yet no study has documented the influence of ethnicity on the cultural use of pangolins. The aim of this study was to determine the influence of ethnicity on the cultural use of pangolins in Ghana. Data on the use of pangolin for traditional medicine were gathered from 300 traditional medicinal practitioners from the major ethnic groups in Ghana through semi-structured individual interviews. Also, 150 chopbar operators were interviewed to determine the level of pangolin bushmeat preferences and consumption amongst the different ethnicity in Ghana. Peculiarities in knowledge, ethnic endogamy, inter-ethnic relations, and segregation in the settlement among the various ethnic groups affected the selection and use report of pangolin body parts and the assemblage of ethnic groups. Certain ethnic groups were very similar to one another in the use of pangolin body parts for traditional remedies but other were clearly different. Ethnicity did not have any influence on the consumption of pangolin bushmeat, however, scarceness of pangolin bushmeat was the main factor that affected the frequency of consumption. The findings of this study highlight the importance of cultural uses of pangolins by different ethnicities and how this information can be used to contribute to the design of a more effective and targeted conservation management strategy for these rare mammals.